A bovine aortic arch in humans - María Elena Arnáiz-García (Indian Heart Journal, 2014)
We describe a curious congenital variation of human aortic arch (AA) branching pattern termed the “bovine aortic arch”. Rather than arising directly from the AA as a separate branch as occurs in the most common AA branching pattern, the left common carotid artery moves to the right and merges from the brachiocephalic trunk. It is the normal AA branching pattern presented in a number of animals (canines, felines or Macaque monkeys) but it has nothing to do with anatomy of AA in ruminant animals, including cattle and buffalo. That is why it is one of the most widely misnomers used in medical literature whose origin is nowadays unknown.